Meeting global industry service quality: Specialised Network Services (SNS) approach & methodlogy / Ruhayu Kartini Mamat (Faculty of Business and Management, 2007)
In this research, the service quality of Specialised Network Services (SNS) is examined. In this study, it examines the service quality dimensions affect sales for every service. From here, the strong and weak factors of Specialised Network Services can be identified. Exploratory research is used in designing this research . Both primary and secondary data are used for the study. This situation of SNS service quality is being observed and interviews with selected customers are conducted. There are 100 questionnaires are being distributed to the customers . The sampling technique is Simple Random Sampling . This finding focuses on whether SNS can meet international service quality. From the analysis, SNS can improve the problem by ensure that the product will be functioned all the time. On top of that, SNS should train its worker so that this technology can be used efficiently without any problem. This research finding help SNS to better understand customers need and want. Hopefully, it helps SNS to improve their performance in futures.